The association between acute myocardial infarction and constipation and progress in nursing care studies (急性心肌梗死与便秘的相关性及护理研究进展) - FAN Yufei (范羽飞); YANG Yang (杨阳); ZANG Yaning (臧亚宁); ZHANG Dan (张丹) (中西医结合护理)
Acute myocardial infarction is myocardial necrosis resulting from acute obstruction of a coronary artery. Various factors including decreased cardiac output, defecation habit changes, drugs affecting gastrointestinal motility, profuse sweating, vomiting and fever increase the risk of constipation in patients with acute myocardial infarction. The constipation may induce cardiovascular events such as angina, heart failure, shock and even sudden death. This paper conducts a review of the literature on the definition and diagnosis of constipation, the association between constipation and cardiovascular events, the factors related to constipation and the preventive and intervention measures that can be taken in acute myocardial infarction patients. The aim of this paper is to further raise the attention of medical professionals to the importance of constipation in acute myocardial infarction and to provide a reference for standardized intervention and management of safe defecation. (急性心肌梗死是冠心病的严重类型。患者由于心肌缺血缺氧坏死, 心输出量不同程度的减少, 卧床排便习惯改变、药物抑制肠蠕动, 大量出汗, 呕吐或发热等症状, 导致便秘成为常见的并发症之一。排便不畅可能诱发心绞痛、心力衰竭、心律失常、休克甚至猝死等心血管事件。因此, 如何预防便秘是AMI患者护理中不容忽视的重要内容。本文对急性心肌梗死合并便秘展开文献回顾, 就便秘的概念、急性心肌梗死与便秘的相关性及便秘的预防、干预措施进行综述, 以期进一步提高医务人员对急性心肌梗死合并便秘的重视程度, 为规范干预措施、安全排便管理提供参考。)